Significance of searching for ganglia in the terminal rectum/fistula of complex anorectal malformations: Related to defecation function - Feng, Wei; Mu, Huaqi; Chen, Minmin; Zhu, Jin; Xiang, Chenzhu; Fan, Linxiao; Hou, Jinping; Die, Xiaohong; Wang, Yi (Frontiers in Pediatrics, 2023)
Background: The necessity of searching for ganglia in the terminal rectum/fistula of complex anorectal malformations (ARMs) still remains controversial. This study aims to evaluate the relationship between ganglia absence in the terminal rectum/fistula and defecation function after anoplasty. Methods: Retrospective review of patients who received anoplasty for treating male imperforate anus with rectobulbar (RB)/rectoprostatic (RP) fistulas at a tertiary pediatric hospital was conducted with registered of demographic data, imaging study results, information of the terminal rectum/fistula specimen (excision extension and pathological findings). According to the pathological findings, patients were divided into Group 1 (ganglia absence) and 2 (ganglia presence). Furthermore, postoperative defecation function was evaluated using various rating scale questionnaires. Statistical analysis was performed using SPSS 22.0. Results: Of the 62 patients, 18 cases (29.0%) showed ganglia absence in the terminal rectum/fistula. By analyzing the imaging data, spinal anomalies and spinal cord anomalies were found in 30.6% (19/62), 56.5% (35/62), respectively. Baseline information was comparable between Group 1 and 2 (P > 0.05). For defecation function, no significant differences in Kelly scores between the two groups (4.0 ± 0.8 vs. 4.4 ± 1.1, P=0.177), while Krickenbeck (3.7 ± 1.8 vs. 5.2 ± 1.4) and Rintala’s (13.7 ± 3.6 vs. 16.0±2.7) scores in Group 1 were significantly lower than that in Group 2 (both P < 0.05). The overall incidence of constipation was 50% (31/62), with Group 1 being higher than Group 2 (77.5% vs. 38.6%, P = 0.002). The area under the curve of ganglia absence for predicting constipation was 0.696, with 77.8% sensitivity and 61.4% specificity. Conclusion: Ganglia absence in the terminal rectum/fistula of male imperforate anus with RB/RP fistulas is associated with constipation after anoplasty, but it has limited predictive value for postoperative constipation. It is necessary to searching for ganglia in the terminal rectum/fistula, both intraoperatively and postoperatively.